A Ampla defesa e o contraditório no processo administrativo disciplinar: uma análise da Súmula Vinculante Nº 5 do STF - CHAVES, Maria do Céu Oliveira (2021)
The Work Research Topic: The Conflict between the Principle of Contradiction and the Comprehensive Defence and Binding Note nº 5 STF, portrays the repeated decisions of the Exalted Supreme Court against the imposition of the need for lawyers in administrative disciplinary interest in protecting the servers from all spheres, for misconduct or not, during the public service. It happens that completely disagrees with the Binding Precedent Precedent nº 343 of the Superior Court, where it is that no damage will the Federal Constitution, the lack of presence of counsel in administrative disciplinary proceedings. Moreover, the LV Clause of Article 5 of CF/88, requires that there be full on defense, with the maintenance of the same, the Lawyers, as described in the Law 8.906 of July 4, 1994 in his art. 3. The conflict is clearly shown between the binding precedent paragraph 5 of the STF and the LV section of Article 5 of CF/88, combined with art. 3 of Law 8.906/94.